Program module for calculating the optimal interval of preventive substitutions - Smirnov, Vladimir U.; Kos, Oksana I. (2017 International Conference "Quality Management,Transport and Information Security, Information Technologies" (IT&QM&IS), 2017)
Railway transport is one of the main transport modes of the Russian Federation, which is strategically important for the country. Artificial constructions on the railways are complex and responsible elements of the track economy. The probability of their failure-free operation must be high enough. For the adoption of optimal solutions for managing the technical state of man-made structures, it is necessary to use probabilistic operating models, build algorithms for calculating reliability and development indices using these algorithms of the software package, which makes it possible to automate the process of controlling the operation of artificial constructions on railways.